Environmental management of waste electrical and electronic equipment - Hussain, Chaudhery Mustansar (Elsevier, 2021)
Environmental Management of Waste Electrical and Electronic Equipment illustrates the socioeconomic, technical and environmental perspectives of WEEE, allowing for a better understanding on how to manage this rapidly growing waste stream. The book addresses discharge of WEEE into ecosystems, occupational exposure to hazardous components of WEEE, and loss of recoverable resources, bridging the gap between community and waste management. By providing in-depth analysis and step-by-step descriptions of environmental strategies and procedures for managing electrical and electronic waste, this book is a valuable resource for environmental scientists, environmental engineers, and waste management professionals to achieve sustainability in WEEE.